2021
DOI: 10.1108/emjb-06-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Culture, institutional quality and earnings management: an international evidence

Abstract: PurposeThis paper examines the link between culture, institutional quality and real earnings management and accrual earnings management by combing the study by Hofstede (2001) and Enomoto et al. (2015). The paper tries to test the effect of culture on institutional quality and both real earnings management (REM) and accrual earnings management (AEM).Design/methodology/approachThe sample of the research paper includes 38 countries. Hofstede cultural dimensions are used to measure cultural values. Public governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…This reveals that improvement in rule of law (law and order) could be used to reduce the level of board politics, corruption, sharp practices, and opportunism in designing efficient and effective executive compensation contracts in Nigeria. This result aligns with the findings of studies such as Yamen et al (2021), Martens et al (2021), Zou (2019) Sepahvand et al (2019), Wijayana and Gray (2019), Jouber and Fakhfakh (2014), Bryan et al (2010, 2011), and Brenner and Schwalbach (2009) which found that institutional quality is a key input in driving executive compensation contracts. This research outcome reveals that institution (law and order) plays an important role in the determination of pay packages of CEOs of listed firms in Nigeria.…”
Section: Presentation and Discussion Of Empirical Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…This reveals that improvement in rule of law (law and order) could be used to reduce the level of board politics, corruption, sharp practices, and opportunism in designing efficient and effective executive compensation contracts in Nigeria. This result aligns with the findings of studies such as Yamen et al (2021), Martens et al (2021), Zou (2019) Sepahvand et al (2019), Wijayana and Gray (2019), Jouber and Fakhfakh (2014), Bryan et al (2010, 2011), and Brenner and Schwalbach (2009) which found that institutional quality is a key input in driving executive compensation contracts. This research outcome reveals that institution (law and order) plays an important role in the determination of pay packages of CEOs of listed firms in Nigeria.…”
Section: Presentation and Discussion Of Empirical Findingssupporting
confidence: 89%
“…Thus, benchmarking pay for performance for CEOs of listed firms has a high likelihood to be mediated by the level of institutions. This connotes that the states of institutions in a country have the potency of mediating executive compensation contracts and the pay‐performance sensitivity for CEOs of quoted firms (Gyapong et al, 2020; Yamen et al, 2021). A country's institutional environment and legal enforcement of contracts are key ingredients in ensuring the effectiveness of CEO pay as a corporate governance tool (Jouber & Fakhfakh, 2011, 2014; Sheikh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results on cultural factors support the findings of Yamen et al (2022). These authors highlight the role of both formal and informal cultures in shaping financial reports.…”
Section: Modelsupporting
confidence: 89%
“…Recent studies have demonstrated that international marketing functions are changing rapidly, due to market dynamism (Jeong et al ., 2019; Liu et al ., 2020; Reimann et al ., 2022). Other studies have highlighted that some theories have potential to explore the concept of IDMCs, but they still require further investigation from the perspective of international marketing abilities (Gligor et al ., 2019; Rust, 2020; Al-Kwifi et al ., 2021; Yamen et al ., 2022; Hoque et al ., 2022a, b; Reimann et al ., 2022). International marketing literature has identified marketing abilities as the main driver of firms' internationalization (Morgan et al ., 2018; Mitręga, 2019).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%